Predictors of Seizure-Related Injuries in an Epilepsy Cohort from North India - Dabla, Surekha (J Epilepsy Res, 2018)
BACKGROUND AND PURPOSE: To identify predictors of seizure-related injury (SRI) and death in people with epilepsy (PWE) in a North Indian cohort. METHODS: This ambispective cohort study included PWE registered in an epilepsy clinic in Delhi between May 2010 and December 2011. Five hundred twenty-six patients were enrolled and followed for 25 months. Patients were categorized into two groups based on SRI/no SRI during the study period. We analyzed various factors to identify predictors of SRI and death. RESULTS: Of 526 patients, 355 (67.5%) reported having no SRIs and 171 (32.5%) had sustained an SRI. Among patients with SRI, 72.5% were male; 62% of those with no SRI were male. The injury type included soft tissue (60%), head trauma (20%), dental trauma (10%), orthopedic (10%), and burns (5%). On univariate analysis, factors predicting SRI occurrence were male gender, abnormal birth history (p < 0.01), abnormal mental status (p < 0.01), seizure duration (p < 0.04), daytime seizures (p < 0.05), dependence on a caregiver (p < 0.008), and uncontrolled seizures (p < 0.001), history of cluster seizures or status epilepticus (p < 0.001), occurrence of generalized tonic-clonic seizures (GTCS), and use of >3 antiepileptic drugs (p < 0.008). On multiple logistic regression analysis, male gender, uncontrolled seizures, history of cluster seizures or status epilepticus, and GTCS were significant risk factors. Sixteen deaths occurred in our cohort, and 13 fit the definition of probable sudden unexpected death in epilepsy (SUDEP). Most patients with SUDEP had an unwitnessed event (69.2%). The only significant factor in predicting death was uncontrolled seizures. CONCLUSIONS: Male gender, occurrence of GTCS, uncontrolled seizures, and history of cluster seizures or status epilepticus predicted SRI occurrence in PWE. Precautions should be taken by caregivers of patients with these risk factors, to prevent injury.